Improving Planting Stocks for the Brazilian Atlantic Forest Restoration through Community-Based Seed Harvesting Strategies - Brancalion, Pedro H. S.; Viani, Ricardo A. G.; Aronson, James; Rodrigues, Ricardo R.; Nave, André G. (Restoration ecology, 2012)
High‐diversity reforestation can help jumpstart tropical forest restoration, but obtaining viable seedlings is a major constraint: if nurseries do not offer them, it is hard to plant all the species one would like. From 2007 to 2009, we investigated five different seed acquisition strategies employed by a well‐established tree nursery in southeastern Brazil, namely (1) in‐house seed harvesters; (2) hiring a professional harvester; (3) amateur seed harvesters; or (4) a seed production cooperative, as well as (5) participating in a seed exchange program. In addition, we evaluated two strategies not dependent on seeds: harvesting seedlings from native tree species found regenerating under Eucalyptus plantations, and in a native forest remnant. A total of 344 native tree and shrub species were collected as seeds or seedlings, including 2,465 seed lots. Among these, a subset of 120 species was obtained through seed harvesting in each year. Overall, combining several strategies for obtaining planting stocks was an effective way to increase species richness, representation of some functional groups (dispersal syndromes, planting group, and shade tolerance), and genetic diversity of seedlings produced in forest tree nurseries. Such outcomes are greatly desirable to support high‐diversity reforestation as part of tropical forest restoration. In addition, community‐based seed harvesting strategies fostered greater socioeconomic integration of traditional communities in restoration projects and programs, which is an important bottleneck for the advance of ecological restoration, especially in developing countries. Finally, we discuss some of the limitations of the various strategies for obtaining planting stocks and the way forward for their improvement.